PENINGKATAN HASIL BELAJAR MATEMATIKA SISWA MELALUI METODE TUTOR SEBAYA DI SMK NAMIRA TECH NUSANTARA MEDAN - abdul halim hasugian (AXIOM : Jurnal Pendidikan dan Matematika, 2017)
This research aim to know: (1) do applying of tutor sebaya method can push student to learn more active, ( 2) do study with tutor sebaya method can improve result learn, ( 3) how perception of student about study with tutor sebaya method. This research represent research of class action. This research subject class XII TKJ-A SMK Namira Tech Nusantara about 31students. Passed to treatment subject in this research is to improve result learn student pass applying of tutor sebaya method in study. Of data analysis indicate that study by applying tutor sebaya method can be seen from result learn student which mounting and result of observation staying in good category. Percentage of complete level learning student by clasical experience about 19,35% and this means that integral lesson pass tutor sebaya method can improve result of learning student.